Gauging students' emotional state amidst open and distance learning (odl) mode - Hasan, Hazlin; Syed Wahid, Sharifah Norhuda; Nikman, Khairunisa; Aminuddin, Azwan Shah; Badruesham, Nurfarawahidah (GADING Journal for the Social Sciences, 2024)
The outbreak of the COVID-19 pandemic worldwide has led Universiti Teknologi MARA (UiTM) management to move all classes for its campuses nationwide to an Open and Distance Learning (ODL) mode starting April 2020. Since then, the shift has brought mixed feelings of distress and uneasiness, and symptoms of mental distress can be seen among students through comments and status updates shared on various social networking sites. The researchers found it significant to investigate students‟ emotional states during ODL mode by measuring their scores on depression, anxiety and stress levels using the DASS-21 questionnaire, as well as to identify the effects of anxiety and stress levels towards depression among the respondents. Primary data was employed involving 848 UiTM Cawangan Pahang students whereby descriptive statistics and structural equation modelling were used to analyze the data. The findings indicated that there existed positive significant effects of stress and anxiety towards depression (β1 =.704, p-value < 0.001; β2 =.113, p-value < 0.01) with 62% total variation explained. The stress factor contributed more effects towards depression compared to the anxiety factor. The findings are aimed at providing new knowledge and discoveries on the issues related to student’s mental health, as well as to offer some insights on how the university’s relevant authorities could assist the students in dealing with the problems.